International Development Policy: Religion and Development - Carbonnier, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The rise of fundamentalist movements in major religions has forced decision-makers, development organizations and academics to turn their attention to its meaning for development. Global scholars and practitioners examine these issues and fundamentally question the secular-religious dichotomy in development discourse and practice.
Keywords: Religion and sociology; Economic development; Economic policy; Poverty; Social Aspects of Religion; Sociology of Religion; Development Studies; Development Policy; Development Aid; Religion and Society